Nursing Care in Close Fracture of Manus Dextra Digiti V Patients - Siti Suciati Nur Khasanah; Tophan Heri Wibowo (Inspirasi Foundation, 2022)
Objective: This study aims to describe changes in pain in patients with 5 finger hypnotic non-pharmacological therapy. Method: This research is a case study that was conducted in March 2022 with an assessment guide instrument for data collection. Researchers used the nursing care process from the assessment stage to evaluation. Result: According to the results of the study, guided relaxation techniques for 3 days can reduce pain, from pain intensity on a scale of 5 to 4. Conclusion: The most felt and disturbing complaint of fracture patients is pain in the area around the wound/fracture with a scale of 5, pain like stabbing. Pain will be felt when the patient moves the fractured part. Non-pharmacological hypnotic therapy of 5 fingers within a period of 3 days is able to reduce the scale of pain felt in postoperative 5 finger digiti fracture patients.